Occupational and Environmental Cancer - Yari, Saeed; Fallah Asadi, Ayda; Nourmohammadi, Mohammad (Asian Pacific Journal of Environment and Cancer, 2018)
Environmental pollution is one of the main causes of disease, death, and disability worldwide. International Labor Organization (ILO) estimates mortality caused by occupational cancer worldwide to be two times higher than occupational accidents. Approximately, 10 important risk factors account for 85% of all occupational cancers. Factors for occupational cancer includes Asbestos, chemicals such as aniline, chromates, dinitrotoluene, arsenic and its inorganic compounds, beryllium and its compounds, cadmium and nickel compounds, wood dust, crystalline silica, brown coal phosphors, furnace emissions, pollution caused by diesel equipment, Nano-Materials, biological agents, ionizing radiation and non-ionizing radiation, thermal shock, shift work, stress and work while sitting. Also some other environmental factors can cause cancer which concludes air, water and soil pollutions, smoking, sunlight, radon gas, electromagnetic fields, agriculture, behavior and lifestyle (such as alcohol and tobacco consumption, diet, sleep patterns, personal habits and social and cultural environment behaviors). More than 75% of mortality due to cancer can be avoided via controlling occupational and environmental risk factors. Most of cancers are not hereditary and caused by occupational and environmental biological agents, and are potentially preventable. So, it is recommended that more researches should be performed in this field in order to detect more scientific and effective methods to detect number and type of cancers due to occupational and environmental factors.